A low-chrome corundum brick, its preparation method and application

By using low-chromium corundum bricks prepared with low-chromium chromium corundum, aluminum-magnesium carbon recycled materials and premixes, the problem of excessive chromium oxide content in existing refractory materials is solved, and the performance and cost reduction of the steel tank base bricks are improved.

CN119306481BActive Publication Date: 2025-04-04HUNAN XIANGGANG RUITAI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411855745.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing refractory materials have too high chromium oxide content during molten steel smelting, which affects the control of molten steel composition and causes pollution to the environment. The purchase price of plate-shaped corundum is high, resulting in high operating costs.

Method used

Low chromium corundum, aluminum-magnesium carbon recycled materials and premixed materials are used to prepare low chromium corundum bricks through specific proportion combinations and phenolic resin as binding agents to replace plate-shaped corundum as the bottom brick of the steel tank.

Benefits of technology

Low-chromium corundum bricks are comparable or better than plate-shaped corundum in terms of performance, with lower operating costs, and reduce pollution to molten steel by reducing chromium oxide content, improving environmental protection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of refractory materials, and in particular to a low-chrome corundum brick, a preparation method and application thereof. The low-chrome corundum brick is prepared from raw materials including component a and an external binder; the component a includes: 25 wt%~35 wt% of low-chrome corundum; 50 wt%~70 wt% of aluminum-magnesium-carbon recycled material; 10 wt%~20 wt% of premix; the sum of the amounts of the components is 100%; in the low-chrome corundum, the mass content of chromium oxide is less than 5%; at the same time, the present invention limits the particle size ratio of low-chrome corundum and aluminum-magnesium-carbon recycled material, and limits the components and content of the premix; the external binder is phenolic resin; the external binder accounts for 2%~3% of the mass of the component a. The low-chrome corundum brick provided by the present invention can replace plate-shaped corundum as a bottom brick for a molten steel tank, and has equivalent or even better performance and lower operating cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a low-chrome corundum brick, a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous development and progress of my country's steelmaking technology, the demand for special steel has increased year by year, and the quality requirements for high-purity and high-cleanliness steel are getting higher and higher. The refining rate of molten steel in the ladle is also increasing. The substantial increase in refining has had a certain impact on the use of existing refractory materials, requiring higher and higher quality refractory materials, including their composition, stability, and anti-scouring performance.

[0003] At present, the main skeleton material of the bottom bricks in the molten steel tank is tabular corundum. Due to the high purchase price of raw materials, the overall operating cost is relatively high. Therefore, it is imperative to develop alternative products with higher cost performance.

[0004] During the steelmaking process, the composition of the molten steel is strictly required. Too high chromium oxide content is not conducive to the composition control of the molten steel. At the same time, the used chromium oxide will cause certain pollution to the environment. Therefore, there are certain requirements for the chromium oxide content in the product, and the used product needs to be effectively treated. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a low-chrome corundum brick, a preparation method and application thereof. The low-chrome corundum brick provided by the present invention can replace plate-shaped corundum as the bottom brick of a molten steel tank, and has equivalent or even better performance and lower operating cost.

[0006] The present invention provides a low-chrome corundum brick, which is prepared from raw materials including component a and an external binder;

[0007] The component a is composed of the following components:

[0008] Low chromium corundum 25 wt%~35 wt%;

[0009] Aluminum magnesium carbon recycled material 50 wt%~70 wt%;

[0010] Premix 10 wt%~20 wt%;

[0011] The sum of the amounts of the components is 100%;

[0012] In the low-chromium chromium corundum, the mass content of chromium oxide is less than 5%;

[0013] The low-chrome chrome corundum is composed of the following components:

[0014] 5~8 mm low chrome corundum 7 wt%~10 wt%;

[0015] 3~5 mm low chrome corundum, excluding 5 mm 7 wt%~10 wt%;

[0016] 1~3 mm low chrome corundum, excluding 3 mm 10 wt%~15 wt%;

[0017] The aluminum-magnesium-carbon regenerated material is composed of the following components:

[0018] 3~5 mm aluminum magnesium carbon recycled material 10 wt%~15 wt%;

[0019] 1~3 mm aluminum magnesium carbon recycled materials, excluding 3 mm 15 wt%~20 wt%;

[0020] 0~1 mm aluminum magnesium carbon recycled materials, excluding 1 mm 25 wt%~35 wt%;

[0021] The premix consists of the following components:

[0022] Fused magnesia 4 wt%~5 wt%;

[0023] Graphite 4 wt%~6 wt%;

[0024] Silicon carbide 1.5 wt%~2 wt%;

[0025] Boron carbide 0.2 wt%~0.4 wt%;

[0026] Resin powder 0.3 wt%~0.58 wt%;

[0027] The external binder is phenolic resin; the external binder accounts for 2% to 3% of the mass of component a.

[0028] Preferably, in the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 15% to 20%, the mass content of magnesium is 60% to 70%, the mass content of carbon is 10% to 20%, and the mass content of ferric oxide is less than 1%;

[0029] The preparation method of the aluminum-magnesium-carbon regenerated material comprises the following steps:

[0030] The magnesia carbon bricks and / or aluminum-magnesium carbon bricks remaining after steel smelting are recovered, sorted, impurity-removed, soaked, dried, crushed and screened to obtain aluminum-magnesium-carbon recycled materials.

[0031] Preferably, the fused magnesia is 96 fused magnesia; the particle size of the fused magnesia is 0.08-0.09 mm.

[0032] Preferably, the graphite is 95 graphite; the particle size of the graphite is 100 mesh.

[0033] Preferably, the silicon carbide is 97 silicon carbide; the particle size of the silicon carbide is 0.07~0.08 mm.

[0034] Preferably, the particle size of the resin powder is 0.08-0.09 mm; and the resin powder is phenolic resin powder.

[0035] Preferably, the method for preparing the premix comprises the following steps:

[0036] The fused magnesia, graphite, silicon carbide, boron carbide and resin powder are mixed to obtain a premix.

[0037] Preferably, the resin comprises at least one of phenolic resin and PF-4326 XG resin.

[0038] The present invention also provides a method for preparing the low-chrome corundum bricks described above, comprising the following steps:

[0039] A) mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials, mixing with phenolic resin for mixing and milling, and then mixing with premixed materials for mixing and milling to obtain mixed milled materials;

[0040] B) forming the mixed material to obtain a carbon brick blank;

[0041] C) baking the carbon brick blank to obtain a low-chrome corundum brick.

[0042] The present invention also provides an application of low-chrome corundum bricks in molten steel tanks;

[0043] The low-chrome corundum brick is the low-chrome corundum brick described above; or is the low-chrome corundum brick prepared by the preparation method described above.

[0044] The raw materials of the low-chrome corundum bricks provided by the present invention use powders of different particle sizes. Through a certain proportion combination, the density of the product produced after mixing can be higher and the porosity can be reduced. The premix is ​​a relatively small but key raw material in the entire formula. Its main function is to improve the high-temperature performance of the product, such as improving the high-temperature flexural strength and enhancing the ability to resist erosion at high temperatures. Resin powder, as a binder, has a promoting effect on improving the above-mentioned properties. The above-mentioned components can cooperate well with each other. As the bottom bricks of molten steel tanks, they have better performance and lower operating costs. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The present invention provides a low-chrome corundum brick, which is prepared from raw materials including component a and an external binder;

[0047] The component a comprises:

[0048] Low chromium corundum 25 wt%~35 wt%;

[0049] Aluminum magnesium carbon recycled material 50 wt%~70 wt%;

[0050] Premix 10 wt%~20 wt%;

[0051] The sum of the amounts of the components is 100%;

[0052] In the low-chromium chromium corundum, the mass content of chromium oxide is less than 5%;

[0053] The low-chrome chrome corundum comprises:

[0054] 5~8 mm low chrome corundum 7 wt%~10 wt%;

[0055] 3~5 mm low chrome corundum, excluding 5 mm 7 wt%~10 wt%;

[0056] 1~3 mm low chrome corundum, excluding 3 mm 10 wt%~15 wt%;

[0057] The aluminum-magnesium-carbon recycled material comprises:

[0058] 3~5 mm aluminum magnesium carbon recycled material 10 wt%~15 wt%;

[0059] 1~3 mm aluminum magnesium carbon recycled materials, excluding 3 mm 15 wt%~20 wt%;

[0060] 0~1 mm aluminum magnesium carbon recycled materials, excluding 1 mm 25 wt%~35 wt%;

[0061] The premix comprises:

[0062] Fused magnesia 4 wt%~5 wt%;

[0063] Graphite 4 wt%~6 wt%;

[0064] Silicon carbide 1.5 wt%~2 wt%;

[0065] Boron carbide 0.2 wt%~0.4 wt%;

[0066] Resin powder 0.3 wt%~0.58 wt%;

[0067] The external binder is phenolic resin; the external binder accounts for 2% to 3% of the mass of component a, such as 3%.

[0068] In certain embodiments of the present invention, the mass content of chromium oxide in the low-chromium chromium corundum is 4.9%, 4.4%, or 4.6%.

[0069] In certain embodiments of the present invention, in the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 15%~20%, such as 17.2% and 16.9%; the mass content of magnesium is 60%~70%, such as 65.5%, 66.2%, and 67.2%; the mass content of carbon is 10%~20%, such as 14.8%, 15.6%, 14.6%, and 14.4%; the mass content of ferric oxide is less than 1%, such as 0.63%, 0.43%, and 0.74%.

[0070] In certain embodiments of the present invention, the method for preparing the aluminum-magnesium-carbon regenerated material comprises the following steps:

[0071] The magnesia carbon bricks and / or aluminum-magnesium carbon bricks remaining after steel smelting are recovered, sorted, impurity-removed, soaked, dried, crushed and screened to obtain aluminum-magnesium-carbon recycled materials.

[0072] The picking is manual picking. The impurity removal can be the removal of steel slag. The crushing adopts a crusher.

[0073] In certain embodiments of the present invention, the fused magnesia is 96 fused magnesia. The particle size of the fused magnesia is 0.08-0.09 mm, such as 0.088 mm.

[0074] In certain embodiments of the present invention, the graphite is 95 graphite. The particle size of the graphite is 100 mesh.

[0075] In some embodiments of the present invention, the silicon carbide is 97 silicon carbide. The particle size of the silicon carbide is 0.07-0.08 mm, such as 0.074 mm.

[0076] In certain embodiments of the present invention, the particle size of the resin powder is 0.08-0.09 mm, such as 0.088 mm. The resin powder is phenolic resin powder.

[0077] In certain embodiments of the present invention, the method for preparing the premix comprises the following steps:

[0078] The fused magnesia, graphite, silicon carbide, boron carbide and resin powder are mixed to obtain a premix.

[0079] The mixing time is 13-17 min, for example 15 min. The mixing is carried out in a mixer.

[0080] In certain embodiments of the present invention, the resin is at least one of phenolic resin and PF-4326 XG resin. The phenolic resin is phenolic resin PF5319.

[0081] The raw materials of the low-chrome corundum brick provided by the present invention use powders of different particle sizes, and through a certain proportion combination, the density of the product produced after mixing can be higher and the porosity can be reduced.

[0082] Premix is ​​a relatively small but key raw material in the entire formula. Its main function is to improve the high temperature performance of the product, such as improving the high temperature flexural strength and enhancing the ability to resist corrosion at high temperatures. Resin powder, as a binder, has a promoting effect on improving the above properties.

[0083] The present invention also provides a method for preparing the low-chrome corundum bricks described above, comprising the following steps:

[0084] A) mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials, mixing with phenolic resin for mixing and milling, and then mixing with premixed materials for mixing and milling to obtain mixed milled materials;

[0085] B) forming the mixed material to obtain a carbon brick blank;

[0086] C) baking the carbon brick blank to obtain a low-chrome corundum brick.

[0087] In certain embodiments of the present invention, the mixing is stirring mixing, and the mixing is performed in an 800 forced sand mixer. The mixing time can be 1 to 3 minutes, such as 2 minutes.

[0088] In certain embodiments of the present invention, the mixing and grinding time with the phenolic resin may be 1 to 3 minutes, such as 2 minutes.

[0089] In certain embodiments of the present invention, the time for mixing and milling with the premix may be 15 to 20 minutes, such as 18 minutes.

[0090] In certain embodiments of the present invention, the molding method is blow molding. Specifically, it can be: blow molding on a 1000-ton press. The number of blows can be 16.

[0091] In certain embodiments of the present invention, the carbon brick blank has a thickness of 90-110 mm, such as 100 mm.

[0092] In certain embodiments of the present invention, the baking temperature is 180-220° C., such as 200° C., and the baking time is 12-16 h, such as 14 h.

[0093] The present invention also provides an application of the low-chrome corundum brick described above, or the low-chrome corundum brick prepared by the preparation method described above, in a molten steel tank, specifically, as a bottom brick of the molten steel tank.

[0094] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0095] The applicant of the present invention creatively discovered that by replacing expensive plate-shaped corundum with cheaper chrome corundum, steel ladle bottom bricks with equivalent or even better performance can be obtained, and the operating cost can be reduced.

[0096] The present invention has developed aluminum-magnesium-carbon bottom bricks for molten steel tanks through a series of research and tests, which have good anti-scouring performance, corrosion resistance and high high-temperature flexural strength.

[0097] The present invention improves the corrosion resistance and service life of the bottom brick material, reduces environmental pollution, reduces costs and improves benefits.

[0098] The present invention adjusts the content of chromium oxide in the chromium corundum raw material and the proportion of chromium corundum in the formula so that the content meets the requirements of the steel plant and reduces the pollution to molten steel. During the molten steel smelting process, chromium oxide is a pollutant for molten steel, so there are relatively few products containing chromium oxide in the industry. Therefore, in the present invention, the mass content of chromium oxide in the raw material is controlled to be lower than 5%, so that the mass content of chromium oxide in the finished product can be guaranteed to be controlled below 2%. During use, the chromium oxide generated by erosion each time is within an acceptable range and will not affect the quality of the components of the molten steel.

[0099] In order to further illustrate the present invention, a low-chrome corundum brick provided by the present invention, its preparation method and application are described in detail below in combination with embodiments, but it should not be understood as limiting the scope of protection of the present invention.

[0100] Example 1

[0101] Low chrome corundum bricks are prepared from raw materials of component a and an external binder;

[0102] The component a is low-chromium chromium corundum, aluminum-magnesium-carbon recycled material and premix;

[0103] Low chrome corundum (5~8 mm low chrome corundum 7 wt%; 3~5 mm low chrome corundum, excluding 5 mm 10 wt%; 1~3 mm low chrome corundum, excluding 3 mm 15 wt%);

[0104] Aluminum-magnesium-carbon recycled materials (3~5 mm aluminum-magnesium-carbon recycled materials 10 wt%; 1~3 mm aluminum-magnesium-carbon recycled materials, excluding 3 mm 14 wt%; 0~1 mm aluminum-magnesium-carbon recycled materials, excluding 1 mm 32 wt%);

[0105] Premix (96 fused magnesia (0.088 mm) 4.5 wt%; 95 graphite (100 mesh) 5 wt%; 97 silicon carbide (0.074 mm) 2 wt%; boron carbide 0.2 wt%; resin powder (0.088 mm, the resin powder is phenolic resin powder) 0.3 wt%));

[0106] The mass content of chromium oxide in the low-chromium chromium corundum is 4.4%.

[0107] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 17.2%, the mass content of magnesium is 65.5%, the mass content of carbon is 14.8%, and the mass content of ferric oxide is 0.63%.

[0108] The external binder is phenolic resin; the external binder accounts for 3% of the mass of component a.

[0109] The preparation method of the low chrome corundum brick:

[0110] 1) After mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials in an 800 forced sand mixer for 2 min, they were mixed with phenolic resin and milled for 2 min, and then mixed with the premix and milled for 18 min to obtain a mixed milled material;

[0111] 2) The mixed material is struck 16 times on a 1000-ton press to obtain a carbon brick blank with a thickness of 100 mm;

[0112] 3) baking the carbon brick blank at 200° C. for 14 h to obtain a low-chromium corundum brick.

[0113] Example 2

[0114] Low chrome corundum bricks are prepared from raw materials of component a and an external binder;

[0115] The component a is low-chromium chromium corundum, aluminum-magnesium-carbon recycled material and premix;

[0116] Low chrome corundum (5~8 mm low chrome corundum 10 wt%; 3~5 mm low chrome corundum, excluding 5 mm 8wt%; 1~3 mm low chrome corundum, excluding 3 mm 12 wt%);

[0117] Aluminum-magnesium-carbon recycled materials (3~5 mm aluminum-magnesium-carbon recycled materials 10 wt%; 1~3 mm aluminum-magnesium-carbon recycled materials, excluding 3 mm 15 wt%; 0~1 mm aluminum-magnesium-carbon recycled materials, excluding 1 mm 33 wt%);

[0118] Premix (96 fused magnesia (0.088 mm) 4.5 wt%; 95 graphite (100 mesh) 5 wt%; 97 silicon carbide (0.074 mm) 2 wt%; boron carbide 0.2 wt%; resin powder (0.088 mm, the resin powder is phenolic resin powder) 0.3 wt%));

[0119] The mass content of chromium oxide in the low-chromium chromium corundum is 4.9%.

[0120] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 17.2%, the mass content of magnesium is 66.2%, the mass content of carbon is 15.6%, and the mass content of ferric oxide is 0.43%.

[0121] The external binder is phenolic resin; the external binder accounts for 3% of the mass of component a.

[0122] The preparation method of the low chrome corundum brick:

[0123] 1) After mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials in an 800 forced sand mixer for 2 min, they were mixed with phenolic resin and milled for 2 min, and then mixed with the premix and milled for 18 min to obtain a mixed milled material;

[0124] 2) The mixed material is struck 16 times on a 1000-ton press to obtain a carbon brick blank with a thickness of 100 mm;

[0125] 3) baking the carbon brick blank at 200° C. for 14 h to obtain a low-chromium corundum brick.

[0126] Example 3

[0127] Low chrome corundum bricks are prepared from raw materials of component a and an external binder;

[0128] The component a is low-chromium chromium corundum, aluminum-magnesium-carbon recycled material and premix;

[0129] Low chrome corundum (5~8 mm low chrome corundum 10 wt%; 3~5 mm low chrome corundum, excluding 5 mm 10 wt%; 1~3 mm low chrome corundum, excluding 3 mm 15 wt%);

[0130] Aluminum-magnesium-carbon recycled materials (3~5 mm aluminum-magnesium-carbon recycled materials 8 wt%; 1~3 mm aluminum-magnesium-carbon recycled materials, excluding 3mm 12 wt%; 0~1 mm aluminum-magnesium-carbon recycled materials, excluding 1 mm 33 wt%);

[0131] Premix (96 fused magnesia (0.088 mm) 4.5 wt%; 95 graphite (100 mesh) 5 wt%; 97 silicon carbide (0.074 mm) 2 wt%; boron carbide 0.2 wt%; resin powder (0.088 mm, the resin powder is phenolic resin powder) 0.3 wt%));

[0132] The mass content of chromium oxide in the low-chromium chromium corundum is 4.6%.

[0133] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 17.2%, the mass content of magnesium is 66.2%, the mass content of carbon is 14.6%, and the mass content of ferric oxide is 0.74%.

[0134] The external binder is phenolic resin; the external binder accounts for 3% of the mass of component a.

[0135] The preparation method of the low chrome corundum brick:

[0136] 1) After mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials in an 800 forced sand mixer for 2 min, they were mixed with phenolic resin and milled for 2 min, and then mixed with the premix and milled for 18 min to obtain a mixed milled material;

[0137] 2) The mixed material is struck 16 times on a 1000-ton press to obtain a carbon brick blank with a thickness of 100 mm;

[0138] 3) baking the carbon brick blank at 200° C. for 14 h to obtain a low-chromium corundum brick.

[0139] Example 4

[0140] Low chrome corundum bricks are made from the following raw materials:

[0141] Low chrome corundum (5~8 mm low chrome corundum 7 wt%; 3~5 mm low chrome corundum, excluding 5 mm 7wt%; 1~3 mm low chrome corundum, excluding 3 mm 10 wt%);

[0142] Aluminum-magnesium-carbon recycled materials (3~5 mm aluminum-magnesium-carbon recycled materials 15 wt%; 1~3 mm aluminum-magnesium-carbon recycled materials, excluding 3 mm 15 wt%; 0~1 mm aluminum-magnesium-carbon recycled materials, excluding 1 mm 34 wt%);

[0143] Premix (96 fused magnesia (0.088 mm) 4.5 wt%; 95 graphite (100 mesh) 5 wt%; 97 silicon carbide (0.074 mm) 2 wt%; boron carbide 0.2 wt%; resin powder (0.088 mm, the resin powder is phenolic resin powder) 0.3 wt%));

[0144] The mass content of chromium oxide in the low-chromium chromium corundum is 4.4%.

[0145] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 16.9%, the mass content of magnesium is 67.2%, the mass content of carbon is 14.4%, and the mass content of ferric oxide is 0.63%.

[0146] The external binder is phenolic resin; the external binder accounts for 3% of the mass of component a.

[0147] The preparation method of the low chrome corundum brick:

[0148] 1) After mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials in an 800 forced sand mixer for 2 min, they were mixed with phenolic resin and milled for 2 min, and then mixed with the premix and milled for 18 min to obtain a mixed milled material;

[0149] 2) The mixed material is struck 16 times on a 1000-ton press to obtain a carbon brick blank with a thickness of 100 mm;

[0150] 3) baking the carbon brick blank at 200° C. for 14 h to obtain a low-chromium corundum brick.

[0151] Comparative Example 1

[0152] The corundum brick is prepared from the raw materials of component b and an external binder;

[0153] The component b is plate-shaped corundum, aluminum-magnesium-carbon recycled material and premix;

[0154] Tabular corundum (5~8 mm low chrome corundum 7 wt%; 3~5 mm tabular corundum, excluding 5 mm 7 wt%; 1~3 mm tabular corundum, excluding 3 mm 10 wt%);

[0155] Aluminum-magnesium-carbon recycled materials (3~5 mm aluminum-magnesium-carbon recycled materials 15 wt%; 1~3 mm aluminum-magnesium-carbon recycled materials, excluding 3 mm 15 wt%; 0~1 mm aluminum-magnesium-carbon recycled materials, excluding 1 mm 34 wt%);

[0156] Premix (96 fused magnesia (0.088 mm) 4.5 wt%; 95 graphite (100 mesh) 5 wt%; 97 silicon carbide (0.074 mm) 2 wt%; boron carbide 0.2 wt%; resin powder (0.088 mm, the resin powder is phenolic resin powder) 0.3 wt%));

[0157] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 15.9%, the mass content of magnesium is 68.2%, the mass content of carbon is 14.4%, and the mass content of ferric oxide is 0.63%.

[0158] The external binder is phenolic resin; the external binder accounts for 3% of the mass of component b.

[0159] The preparation method of the corundum brick:

[0160] 1) Plate-shaped corundum (wherein the content of aluminum oxide is 86 wt%, calcium oxide is 1.2 wt%, magnesium oxide is 4.5 wt%, and chromium oxide is not contained) and aluminum-magnesium-carbon regenerated material are mixed in an 800 forced sand mixer for 2 min, mixed with phenolic resin, mixed and milled for 2 min, and then mixed with the premixed material, mixed and milled for 18 min to obtain a mixed milled material;

[0161] 2) The mixed material is struck 16 times on a 1000-ton press to obtain a carbon brick blank with a thickness of 100 mm;

[0162] 3) baking the carbon brick blank at 200° C. for 14 h to obtain a corundum brick.

[0163] Comparative Example 2

[0164] The difference from Example 4 is:

[0165] The low-chromium chromium corundum comprises 10 wt% of particles with a diameter of 3 to 5 mm (excluding particles with a diameter of 5 mm); 10 wt% of particles with a diameter of 1 to 3 mm (excluding particles with a diameter of 3 mm); and 4 wt% of particles with a diameter of 0.088 to 1 mm (excluding particles with a diameter of 1 mm).

[0166] The remaining steps and parameters are the same as those in Example 4; a low-chrome corundum brick is obtained.

[0167] Comparative Example 3

[0168] The difference from Example 4 is:

[0169] The aluminum-magnesium-carbon recycled material comprises 15 wt% of particles of 5-8 mm, 15 wt% of particles of 3-5 mm (excluding particles of 5 mm), and 34 wt% of particles of 1-3 mm (excluding particles of 3 mm).

[0170] The remaining steps and parameters are the same as those in Example 4; a low-chrome corundum brick is obtained.

[0171] Comparative Example 4

[0172] The difference from Example 4 is:

[0173] In the aluminum-magnesium-carbon recycled material, the mass content of aluminum is 45.9%, the mass content of magnesium is 38.2%, the mass content of carbon is 14.4%, and the mass content of ferric oxide is 0.63%.

[0174] The remaining steps and parameters are the same as those in Example 4; a low-chrome corundum brick is obtained.

[0175] The properties of the corundum bricks prepared in Examples 1 to 4 and Comparative Example 1 were tested, and the results are shown in Table 1. Specifically, "temperature*time" in Table 1 means that the prepared corundum bricks are baked (heat treated) at the temperature for a corresponding time, and then the baked corundum bricks are tested.

[0176] Table 1 Properties of the corundum bricks obtained in Examples 1 to 4 and Comparative Example 1 after heat treatment

[0177]

[0178] It can be seen from Table 1 that after comparing the test data, analyzing the line changes and comprehensive test data of corundum bricks at high temperatures, the indicators of Example 4 better meet the requirements, and compared with the plate-shaped corundum of Comparative Example 1, the high-temperature performance is similar, and the raw material cost of the present invention is relatively low (the price of plate-shaped corundum is 6000-6500 yuan / ton, and the price of low-chromium corundum is 2800-3200 yuan / ton), and it is more cost-effective as a bottom brick in a molten steel tank.

[0179] The properties of the corundum bricks prepared in Comparative Examples 2 to 4 were tested, and the results are shown in Table 2. Specifically, "temperature*time" in Table 2 means that the prepared corundum bricks are baked (heat treated) at the temperature for a corresponding time, and then the baked corundum bricks are tested.

[0180] Table 2 Performance of the corundum bricks obtained in Comparative Examples 2 to 4 after heat treatment

[0181]

[0182] Compared with Example 4, the re-sintering line change (expansion coefficient) of Comparative Examples 2 to 4 is too small, and the performance of the corundum bricks is significantly worse.

[0183] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A low-chrome corundum brick, prepared from component a and an external binder; The component a is composed of the following components: Low chromium corundum 25 wt%~35 wt%; Aluminum magnesium carbon recycled material 50 wt%~70 wt%; Premix 10 wt%~20 wt%; The sum of the amounts of the components is 100%; In the low-chromium chromium corundum, the mass content of chromium oxide is less than 5%; The low-chrome chrome corundum is composed of the following components: 5~8 mm low chrome corundum 7 wt%~10 wt%; 3~5 mm low chrome corundum, excluding 5 mm 7 wt%~10 wt%; 1~3 mm low chrome corundum, excluding 3 mm 10 wt%~15 wt%; The aluminum-magnesium-carbon regenerated material is composed of the following components: 3~5 mm aluminum magnesium carbon recycled material 10 wt%~15 wt%; 1~3 mm aluminum magnesium carbon recycled materials, excluding 3 mm 15 wt%~20 wt%; 0~1 mm aluminum magnesium carbon recycled materials, excluding 1 mm 25 wt%~35 wt%; The aluminum-magnesium-carbon recycled material has an aluminum content of 15% to 20%, a magnesium content of 60% to 70%, a carbon content of 10% to 20%, and a ferric oxide content of less than 1%. The premix consists of the following components: Fused magnesia 4 wt%~5 wt%; Graphite 4 wt%~6 wt%; Silicon carbide 1.5 wt%~2 wt%; Boron carbide 0.2 wt%~0.4 wt%; Resin powder 0.3 wt%~0.58 wt%; The external binder is phenolic resin; the external binder accounts for 2% to 3% of the mass of component a.

2. The low chrome corundum brick according to claim 1, characterized in that: The preparation method of the aluminum-magnesium-carbon regenerated material comprises the following steps: The magnesia carbon bricks and / or aluminum-magnesium carbon bricks remaining after steel smelting are recovered, sorted, impurity-removed, soaked, dried, crushed and screened to obtain aluminum-magnesium-carbon recycled materials.

3. The low chrome corundum brick according to claim 1, characterized in that: The fused magnesia is 96 fused magnesia; the particle size of the fused magnesia is 0.08-0.09 mm.

4. The low chrome corundum brick according to claim 1, characterized in that: The graphite is 95 graphite; the particle size of the graphite is 100 mesh.

5. The low chrome corundum brick according to claim 1, characterized in that: The silicon carbide is 97 silicon carbide; the particle size of the silicon carbide is 0.07-0.08 mm.

6. The low chrome corundum brick according to claim 1, characterized in that: The particle size of the resin powder is 0.08-0.09 mm; the resin powder is phenolic resin powder.

7. The low chrome corundum brick according to claim 1, characterized in that: The preparation method of the premix comprises the following steps: The fused magnesia, graphite, silicon carbide, boron carbide and resin powder are mixed to obtain a premix.

8. The low chrome corundum brick according to claim 1, characterized in that: The resin includes at least one of phenolic resin and PF-4326XG resin.

9. The method for preparing the low-chrome corundum brick according to any one of claims 1 to 8, comprising the following steps: A) mixing low-chrome chrome corundum and aluminum-magnesium-carbon recycled materials, mixing with phenolic resin for co-milling, and then mixing with premixed materials for co-milling to obtain a mixed milling material; B) forming the mixed material to obtain a carbon brick blank; C) baking the carbon brick blank to obtain a low-chrome corundum brick.

10. Application of low chrome corundum brick in molten steel tank; The low-chrome corundum brick is the low-chrome corundum brick according to any one of claims 1 to 8; Or it is a low-chrome corundum brick prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Ladle base brick and production method thereof

    CN107805059A

  • Steel ladle alumina-magnesia carbon brick produced by using waste alumina-magnesia carbon brick and preparation method of steel ladle alumina-magnesia carbon brick

    CN118307308A